Multiple identities and crime: A study of Antillean women and girls in the Netherlands - Althoff, Martina (European Journal of Criminology, 2013)
The concept of intersectionality refers to the constructionist approach, which considers gender, class and race as categories of social inequality that cannot be added together but that intersect and construct each other. Social categories construct the social identities that affect what motivates people and how they operate. The question is how multiple identities come together in the context of crime? The paper reports the findings of a qualitative study that explored the concept of intersectionality when analysing crime. The study analysed the court files of Antillean women and girls living in the Netherlands and tried to find an explanation for their crime patterns in their struggle with their identity.
Keywords: antilles; approches et analyses; criminologie; discipline; europe; femmes* immigrantes; genre; identités LGBTQIA2+; identités de genre; intersectionnalité; inégalités; pays-bas; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppression; thématiques; violences; étude qualitative

Decolonizing feminism: Challenging connections between settler colonialism and heteropatriarchy - Arvin, Maile; Tuck, Eve; Morrill, Angie (Feminist Formations, 2013)
The article explores two intertwined ideas: that the United States is a settler colonial nation-state and that settler colonialism has been and continues to be a gendered process. The article engages Native feminist theories to excavate the deep connections between settler colonialism and heteropatriarchy, highlighting five central challenges that Native feminist theories pose to gender and women's studies. From problematizing settler colonialism and its intersections to questioning academic participation in Indigenous dispossession, responding to these challenges requires a significant departure from how gender and women's studies is regularly understood and taught. Too often, the consideration of Indigenous peoples remains rooted in understanding colonialism as an historical point in time away from which our society has progressed. Centering settler colonialism within gender and women's studies instead exposes the still-existing structure of settler colonialism and its powerful effects on Indigenous peoples and settlers. Taking as its audience practitioners of both "whitestream" and other feminisms and writing in conversation with a long history of Native feminist theorizing, the article offers critical suggestions for the meaningful engagement of Native feminisms. Overall, it aims to persuade readers that attending to the links between heteropatriarchy and settler colonialism is intellectually and politically imperative for all peoples living within settler colonial contexts.
https://www.feministformations.org
Keywords: OFDIG; amériques; approches et analyses; colonialisme; féminisme autochtone; féminisme décolonial; intersectionnalité; militance; patriarcat; ressource en ligne; régions géographiques; systèmes d'oppression; thématiques; états-unis

Deconstructing privilege: Teaching and learning as allies in the classroom - Case, Kim (Routledge, 2013)
Although scholarly examinations of privilege have increased in recent decades, an emphasis on privilege studies pedagogy remains lacking within institutions. This edited collection explores best practices for effective teaching and learning about various forms of systemic group privilege such as that based on race, gender, sexuality, religion, and class. Formatted in three easy-to-follow sections, Deconstructing Privilege charts the history of privilege studies and provides intersectional approaches to the topic. Drawing on a wealth of research and real-life accounts, this book gives educators both the theoretical foundations they need to address issues of privilege in the classroom and practical ways to forge new paths for critical dialogues in educational settings. Combining interdisciplinary contributions from leading experts in the field– such as Tim Wise and Abby Ferber– with pedagogical strategies and tips for teaching about privilege, Deconstructing Privilege is an essential book for any educator who wants to address what privilege really means in the classroom.
Keywords: amériques; approches et analyses; discipline; intersectionnalité; inégalités; justice sociale; outils; ouvrages de références; privilèges; régions géographiques; sciences de l'éducation; systèmes d'oppression; états-unis

Les filles en série: des Barbies aux Pussy Riot - Delvaux, Martine (Les éditions du remue-ménage, 2013)
Des corps féminins en rangées, qui se meuvent en synchronie. Ils ne se distinguent que par le détail d’un vêtement, d’une courbe, d’une teinte de cheveux. Les filles en série créent l’illusion de la perfection. Ce sont des filles-machines, filles-marchandises, filles-ornements. Toutes reproduites mécaniquement par l’usine ordinaire de la misogynie. Les filles sont des filles parce qu’elles sont en série. Mais la figure des filles en série est double: à la fois serial girls et serial killers de l’identité qu’on cherche à leur imposer. Entre aliénation et contestation, les filles en série résistent à leur chosification, cassent le party, libèrent la poupée et se mettent à courir. Cet essai percutant, paru pour la première fois en 2013, se déploie comme une chaîne qui se fait et se défait, depuis les Cariatides jusqu’aux Pussy Riot. Dans cette édition revue et augmentée, Martine Delvaux s’attaque à la blancheur des filles en série et analyse de nouvelles formes de résistance investies par les ballerines, les survivantes d’agressions et Beyoncé.
Keywords: approches et analyses; corps; discipline; discours dominant; fem1000; histoire de l'art; histoire et politique; hétéronormativité; identités LGBTQIA2+; intersectionnalité; militance; premier cycle; systèmes d'oppression; thématiques; études culturelles; études littéraires

Où en sommes-nous avec l'art féministe? : analyse de la programmation de la Centrale Galerie Powerhouse (1973-1978 et 2007-2010) - Rondeau, Kim (Université du Québec à Montréal, 2013)
Au cours des 10 dernières années, de nombreux évènements en arts visuels se sont penchés sur la question du féminisme, malgré l'annonce de la mort de ce courant politique par plusieurs discours populaires. Effectivement, l'avènement, à la fin de la décennie 1980, des champs d'études queer et postcoloniales reconceptualise et complexifie le sujet du féminisme, la femme. Les fondements de l'identité femme, la fixité de cette catégorie, se voient maintenant interroger. De ce fait, les prémisses misent de l'avant par les féministes des années 1970, moment fort du mouvement de libération des femmes, reçoivent un lot important de critique. Dans un tel contexte, nous souhaitons questionner l'art féministe actuel et comment il se manifeste. Plus spécifiquement, nous voulons analyser de quelle façon il diffère des pratiques féministes inaugurés dans la décennie 1970. C'est sur cette problématique que s'attarde ce mémoire prenant pour corpus d'études les expositions présentées, de 1973 à 1978 et de 2007 à 2010, au centre d'artistes féministes montréalais La Centrale Galerie Powerhouse. Ce lieu de diffusion, fondé par des femmes désirant avoir un endroit pour exposer leur art à un moment où elles étaient exclues des institutions, est un témoin privilégié des relations qu'entretiennent le discours artistique et les théories féministes. La Centrale Powerhouse a d'ailleurs modifié son mandat en 2008 dans le but de demeurer pertinent face aux changements ayant lieu au sein du courant féministe. À travers notre étude comparative de la programmation du centre d'artistes, nous voulons démontrer des démarches politisées, enrichies par de nouvelles préoccupations queer et postcoloniales, demeurent possible ainsi qu'une lecture féministe des œuvres. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Art féministe, art contemporain, La Centrale Galerie Powerhouse
Keywords: IREF; amériques; analyse comparée; approches et analyses; art féministe; arts; discipline; histoire de l'art; intersectionnalité; mémoires/thèses; queer; québec; ressource en ligne; régions géographiques